Development of an Online Inventory System for the Engineering and Sciences Laboratory Office of Asia Pacific College through a Mobile Application with Equipment Serial Number Detection using OCR - Villarroel, Juan Miguel; De Jesus, Luigi Carlo M.; Baylon, Bea Daphne B.; Beduya, Rissa Mikaela G.; Verzon, Jayson T.; Samaniego Jr., Leonardo A.; Peruda Jr., Sergio R.; Brucal, Stanley Glenn E.; Yong, Einstein D.; Cosio, Paulo (International Journal of Computing Sciences Research, 2023)
Purpose – The Asia Pacific College’s School of Engineering (APC-SoE) strongly establishes theories to its students and integrating all their theoretical knowledge through projects. Since the students need both software applications and hardware components, the Engineering and Sciences Laboratory Office (ESLO) supports them their needs and at the same time – is responsible for the maintenance of the said necessities. The ESLO, though capable of its duties, still does not have an inventory system to easily track each equipment. The developed application called SoE Keep is created for the ESLO to keep track of equipment that needs recalibration, create, edit, and delete equipment from the database, view reports that shows damaged, borrowed, approved, and returned items that students used. Methodology – The SoE Keep application was developed using Android Studio to work on devices using Android API 7.1.1 and newer version. SoE Keep’s database is directly tied up to the database used by the ESLO Web Services to update the inventory and generate charts pertaining to the statistics of each item. Furthermore, the application uses Android OpenCV to perform the Optical Character Recognition (OCR) function. The OCR includes preprocessing tools such as masking and grayscale transformation for feature extraction. Result – The developed application was evaluated using its accuracy, reliability and its user-friendliness. The application got a 91.67% accuracy rating that is interpreted as a “Good” result. In terms of reliability, the application had a rating of 94.07% that is also interpreted as “Good”. The user-friendliness result was grouped into the set of possible users of the application: ESLO Head/Professors and Student Assistants. Furthermore, it had two sub-categories: Overall Experience and Overall Design. The overall experience of the student assistants was rated 3.78 and the overall design is 3.43. For the ESLO Head and Professors, the overall experience rated 4.8 and the overall design is 4.6. Conclusion – The application developed resulted to the following conclusions that: it was able to have a good accuracy in capturing the serial numbers through an OCR, it also has a good reliability covering the precision of obtaining the correct serial numbers, good overall design and overall experience using the application for the Student Assistants, good overall design and overall experience using the application for the ESLO Head/Professors. Recommendation – The following are the recommendations that must be taken into consideration: collecting more sample data in testing can further increase the precision of the Accuracy and Reliability ratings, improving the overall User Interface and User Experience of the application, improving the usability of the bounding box for capturing the image, improving the graphical visualizations and provide other options for viewing the data such as lists. Practical Implications – SoE Keep, in compliance with ISO 2600 standard, provides practical assistance in implementing social obligations while considering cultural, sociological, environmental, and legal variations as well as economic development situations.